Names of Diseases and Painful Conditions in Publication of V. M. Florinsky “Russian Common Folk Herbalists and Healers”: Composition, Word-Formation Models - O. N. Antsiferova (Научный диалог)
The book “Russian common folk herbalists and healers: a collection of medical manuscripts of the 16th and 17th centuries”, published by Professor V. M. Florinsky (Kazan, 1879) is analyzed. The importance of the study of written monuments of medical content for studying the history of the formation of Russian medical terminology is emphasized. The importance of studying the “Herbalist” and the “Book called cool garden” included in the collection of Florinsky is substantiated. The uniqueness of the language situation in which the named monuments were created is noted - the end of the XVII - the beginning of the XVIII centuries. The objectives of the study are listed. They include identifying the names of diseases and disease states. Word-formation models characteristic of these items are described. Nominative phrases are considered, which play the role of preterm in the professional speech of physicians. It is concluded that the processes of term formation in the Russian medical field, as well as descriptions of painful conditions, were carried out at first using the resources of the mother tongue, which coincided with the idea of the national language norm. Attention is drawn to the fact that the combination of Russianisms, Slavisms and borrowed words in the sources studied can serve as confirmation of the hypothesis about the formation of a new book type of language in which the stylistic neutralization of the genetic differences of lexemes begins.